The Relationship Between Periodontal Status and Blood Glucose Levels in Gestational Diabetes Mellitus - Sepriana Urianti; Aryudhi Armis; Desi Andriyani (CV. CENDIKIA JENIUS INDONESIA, 2025)
Periodontal disorders during pregnancy are often overlooked, despite their potential association with systemic conditions such as Gestational Diabetes Mellitus (GDM). Hormonal changes during pregnancy may trigger gingival inflammation, which can worsen periodontal status, especially in the presence of elevated blood glucose levels. This study aimed to determine the relationship between periodontal status and blood glucose levels in pregnant women. An observational analytic study with a cross-sectional design was conducted. The population consisted of 169 pregnant women at community health centers (Puskesmas) in Bandar Lampung, with 50 participants selected using purposive sampling. Data were collected through clinical examinations, interviews, and documentation from July to September 2023. Data analysis used chi-square and Fisher’s exact tests. The results showed that 6% of respondents with high blood glucose levels had periodontitis, and 10% had gingivitis. Meanwhile, among those with normal blood glucose levels, 10% had periodontitis and 70% had gingivitis. The chi-square test revealed a significant association (p=0.003) between periodontal status and blood glucose levels. It can be concluded that higher blood glucose levels are associated with poorer periodontal conditions. Routine periodontal screening and oral health education for pregnant women with GDM are strongly recommended.